Reduced bone mineral density among HIV-infected, virologically controlled young men: prevalence and associated factors. (28th November 2018) - Shaiykova, Arnoo; Pasquet, Armelle; Goujard, Cécile; Lion, Georges; Durand, Emmanuel; Bayan, Tatiana; Lachâtre, Marie; Choisy, Philippe; Ajana, Faïza; Bourdic, Katia; Viget, Nathalie; Riff, Bertrand; et al.
Abstract : Objective: Reduced bone mineral density (BMD) is a frequent comorbidity observed in people living with HIV (PLHIV). We aimed to determine the prevalence of reduced BMD and its associated factors among young PLHIV men, virologically controlled by combination antiretroviral therapy (cART). Design: A bicentric cross-sectional study. Methods: We selected men, aged less than 50 years, treated by cART, with HIV-RNA less than 50 copies/ml. BMDs of lumbar spine and hip were measured by dual-energy X-ray absorptiometry (DXA). A Z -score at either site between −1.0 and −2.0 or −2 or less defined osteopenia or osteoporosis, respectively. Linear and polytomous logistic regression analyses were performed. Results: Among 230 men with a median age of 43 [interquartile range (IQR), 36–47] years, BMI of 23.5 (21.3–25.3) kg/m 2 and median duration of cART of 4.2 (1.7–8.5) years, reduced BMD was diagnosed in 48.3%. In multivariate analyses, BMI decrease was associated with a risk of osteopenia [odds ratio (OR) = 1.17, P < 0.01] and osteoporosis (OR = 1.24, P < 0.01). Oestradiol levels decrease were associated with osteoporosis (OR = 1.32, P < 0.05) and lower lean mass with osteopenia (OR = 2.98, P < 0.01). There was a protective effect of the duration of cART (OR = 0.87, P < 0.01), which was even greater when the duration was more than 3 years (OR = 0.44, P = 0.02). Conclusion: There is a high prevalence of reduced BMD among young men, despite persistent virological control of HIV-infection. This observation raises the question of extending current recommendations for BMD assessment to PLHIV aged < 50 years for whom BMD has stabilized after cART initiation, i.e. treated for more than three years.